Breaking the Barrier in Endoscopy - Pal, Partha; Ramchandani, Mohan; Pradev, Inavolu; Singh, Aniruddha Pratap; Reddy, Duvvuru Nageshwar (Journal of Digestive Endoscopy, 2021)
In this narrative review, invited by the Editors of the Journal of Digestive Endoscopy, we summarize recent advances in the field of gastrointestinal endoscopy with regard to reaching the earlier inaccessible areas in the gut by newer methods and technology. This article primarily discusses recent advances in the past few years in the following headings: (1) reaching redundant small bowel via enteroscopy (primarily motorized spiral enteroscopy), (2) reaching the thin pancreaticobiliary ducts via cholangioscopy and pancreatoscopy, (3) going out of the gut wall: third-space endoscopy (primarily peroral endoscopic myotomy: POEM). A thorough literature review was performed on each topic describing how the advances were evolving.
Keywords: deep enteroscopy; motorized spiral enteroscopy; cholangioscopy; pancreatoscopy; third-space endoscopy; peroral endoscopic myotomy